Acute Anterior Uveitis in Sydney. (19th December 2012) - Karaconji, Tanya; Maconochie, Zoe; McCluskey, Peter
Abstract: Purpose : To evaluate the patterns of acute and recurrent acute anterior uveitis (AAU) in a metropolitan tertiary referral center. Methods : A retrospective medical record review of a total of 241 patients with AAU presenting to Sydney Eye Hospital between June 2009 and June 2011 was performed. Patients who underwent typing for the HLA-B27 antigen were included in this study. Ninety-five patients were HLA-B27-positive and 146 were HLA-B27-negative. Results : Seronegative spondyloarthropathy ( n  = 26, 11%) was the most common systemic disease association in the HLA-B27 positive patients. Posterior synechiae was the most common complication. Complications of cataract, ocular hypertension, secondary glaucoma, and cystoid macular edema were more common in HLA-B27-negative patients with a recurrent disease course. The most common newly diagnosed systemic disease was sarcoid ( n  = 7), followed by ankylosing spondylitis ( n  = 4), tuberculosis ( n  = 2), and syphilis ( n  = 2). Conclusions : This case series emphasizes the key role of the ophthalmologist in identifying previously undiagnosed systemic diseases. It also highlights the importance of differentiating latent from active infection, particularly tuberculosis and syphilis, through directed investigations to assess the risk to the patient of reactivation with systemic treatment. This study adds further evidence to our understanding that HLA-B27-negative patients have a poor visual prognosis.